2016
DOI: 10.1155/2016/5472601
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Solubilization Potential of Rhizosphere Fungi Isolated from Plants in Jimma Zone, Southwest Ethiopia

Abstract: Phosphorus (P) is one of the major bioelements limiting agricultural production. Phosphate solubilizing fungi play a noteworthy role in increasing the bioavailability of soil phosphates for plants. The present study was aimed at isolating and characterizing phosphate solubilizing fungi from different rhizospheres using both solid and liquid Pikovskaya (PVK) medium. A total of 359 fungal isolates were obtained from 150 rhizosphere soil samples of haricot bean, faba bean, cabbage, tomato, and sugarcane. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(53 citation statements)
references
References 27 publications
2
46
0
5
Order By: Relevance
“…This may be due to the efficiency of Aspergillus spp. in root colonisation as reported by Nenwani et al (2010) and Elias et al (2016).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…This may be due to the efficiency of Aspergillus spp. in root colonisation as reported by Nenwani et al (2010) and Elias et al (2016).…”
Section: Resultssupporting
confidence: 67%
“…The possible reason for these anomalous behaviours on liquid and solid media could be attributed to nutrient availability, varying diffusion rates of different organic acids secreted by fungi, and growth requirement of fungi (Jain et al 2014). The results concluded that for the selection of efficient PSF isolates, the screening should be done on both solid and liquid media (Johri et al 1999;Alam et al 2002;Elias et al 2016). Two P- a) The value of soluble P is a means ± standard error (n = 3).…”
Section: Micro-determination Of Phosphorusmentioning
confidence: 98%
“…Another report on rhizosphere fungi isolated from plants in Jimma Zone, Southwest Ethiopia, showed that 46.52 % isolates are capable of solubilizing inorganic phosphate with solubilization index ranged from 1.1 to 3.05. However, there was no report on their effect on plant growth (Elias et al 2016).…”
Section: Iaa Production and Phosphate Solubilazion Propertiesmentioning
confidence: 99%
“…En otro estudio, Yasser et al (2014) informaron sobre la solubilización de Ca 3 (PO 4 ) 2 por micromicetos de suelos egipcios con valores de IS de 1.08 a 1.45, destacando las especies Aspergillus japonicus (1.45), Aspergillus niger (1.12), Penicillium expansum (1.20), Penicillium funiculosum (1.40), Penicillium variable (1.13) y Penicillium purporogenum (1.30). Recientemente, Elias et al (2016) obtuvieron IS de 1.10 a 3.05 con aislamientos nativos de suelos etíopes, que en su mayoría fueron aislamientos de los géneros Penicillium y Aspergillus. En ambos estudios se reportaron IS menores a los obtenidos por los aislamientos SP5 (5.6) y SP11 (5.0, Penicillium sp.)…”
Section: Crecimiento Fúngico Y Solubilización De Ca 3 (Po 4 ) 2 En Plunclassified